DRAINAGE SYSTEM DESIGN OF GEDEBAGE MUSIC HALL - ARNOLD ARYO YUDANTO - NIM : 15014144, EDUARDUS
Drainage is defined as curvaceous, water channel on the surface or under ground which is form naturally or artificially. Drainage is draining, dewatering, removal, or water diversion. Drainage plays an important role for regulating water supply as flood prevention. Drainage is also defined as an effort to control groundwater quality in relation to sanitation. (Dr. Ir Suripin, M.Eng.2004) The purpose of this final project is to design the drainage system plan for Gedebage Music Hall Bandung, West Java. Data and information that is used is secondary data that obtained from BBWS Citarum for all rain station along Citarum river and BMKG Online Data on rainfall data for at least 10 years. Primary data is obtained from the architectural drawings. Data processing method is using manual calculation with details of Normal Distribution Method, Log Normal Distribution, Log Pearson Type III or Gumbel method. Rainfall intensity is calculated using the equation periodic Mononobe and discharge runoff calculated using Rational Method. Drainage capacity is calculated using Manning equation, then the drainage capacity is evaluated whether or not able to accommodate the discharge of runoff that occurs. The design criteria is used the local drainage system with a return period of 20 years. From the results of the design calculations drainage then it will get some drainage channels with a wide base and height specifications in accordance with the criteria. Channel cross section rectangular and closed by using concrete materials.